2019
DOI: 10.1126/science.aav7062
|View full text |Cite
|
Sign up to set email alerts
|

Restriction of PD-1 function by cis -PD-L1/CD80 interactions is required for optimal T cell responses

Abstract: Targeted blockade of PD-1 with immune checkpoint inhibitors can activate T cells to destroy tumors. PD-1 is believed to function mainly at the effector, but not in the activation, phase of T cell responses, yet how PD-1 function is restricted at the activation stage is currently unknown. Here we demonstrate that CD80 interacts with PD-L1 in cis on antigen-presenting cells (APCs) to disrupt PD-L1/PD-1 binding. Subsequently, PD-L1 cannot engage PD-1 to inhibit T cell activation when APCs express substantial amou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
269
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 300 publications
(288 citation statements)
references
References 40 publications
18
269
1
Order By: Relevance
“…From a translational standpoint, the authors introduced novel pH‐dependent anti‐VISTA antibodies, but showed neither a therapeutic advantage of these clones over the ‘conventional’ anti‐VISTA antagonists nor a reduction in adverse events. Based on recent findings of PD‐L1 cis ‐interactions with CD80 on myeloid cells and its profound functions in regulating immunity , and the very similar of PSGL1 and VISTA expression on the same leukocyte populations, one can reasonably hypothesize that these two proteins may be interacting (in cis ) on the same cell‐forming heterodimers and may both be required for co‐signalling in some contexts. Utilization of available VISTA‐deficient and PSGL‐1‐deficient mice could readily address these questions.…”
Section: The Vista Ligand Mysterymentioning
confidence: 99%
“…From a translational standpoint, the authors introduced novel pH‐dependent anti‐VISTA antibodies, but showed neither a therapeutic advantage of these clones over the ‘conventional’ anti‐VISTA antagonists nor a reduction in adverse events. Based on recent findings of PD‐L1 cis ‐interactions with CD80 on myeloid cells and its profound functions in regulating immunity , and the very similar of PSGL1 and VISTA expression on the same leukocyte populations, one can reasonably hypothesize that these two proteins may be interacting (in cis ) on the same cell‐forming heterodimers and may both be required for co‐signalling in some contexts. Utilization of available VISTA‐deficient and PSGL‐1‐deficient mice could readily address these questions.…”
Section: The Vista Ligand Mysterymentioning
confidence: 99%
“…This has also been corroborated by enhanced activation, although only observable for late readouts such as 41BB expression and target cell killing (Figure 5D). Interestingly we saw an enhanced expression of PDL-1 (Figure 5- Supplement Figure 1B), the ligand for PD-1, on CD8 T-cells, which could lead to cis interactions that act as a cell intrinsic regulation mechanism 25 . Surprisingly, we noted that there are differences between the pathways enhanced by the two blocking antibody clones where EH12 seems superior at enhancing surface markers, whereas Nivolumab outperforms EH12 in the killing assays.…”
Section: Resultsmentioning
confidence: 93%
“…In humans, overexpression of some checkpoint proteins can block surface expression of heterophilic binding partners in cis (e.g. CD80 and PDL1) 42, 43 . As a potential route for disrupting the inhibitory effects of CD200 on anti-tumor immunity, we tested if overexpression of CD200R1 on DFT cells could reduce CD200 surface expression.…”
Section: Resultsmentioning
confidence: 99%